DETERMINATION OF THE ANNUAL ECONOMIC EFFICIENCY OF VIBRATING ROLLERS COMPENSATION (Web of Technology: Multidimensional Research Journal, 2025)
The article presents the economic efficiency indicators achieved as a result of implementing the technological process of one of the compaction machines, the road roller, based on the basic and new recommendations, expressions for determining the parameters involved in ensuring these indicators are given. When calculating the economic efficiency, the technological parameters of the compacting machines and soil properties were taken into account, and indicators were determined for each type of soil.